Simultaneous and cost-effective determination of ethylene glycol and glycolic acid in human serum and urine for emergency toxicology by GC-MS - Hložek, Tomáš; Bursová, Miroslava; Čabala, Radomír (Clinical biochemistry, 2015)
OBJECTIVES: A simple, cost-effective, and fast gas chromatography method with mass spectrometry detection (GC-MS) for simultaneous measurement of ethylene glycol, 1,2-propylene glycol and glycolic acid was developed and validated for clinical toxicology purposes. DESIGN AND METHODS: Successful derivatization of glycolic acid with isobutyl chloroformate was achieved directly in serum/urine while glycols are simultaneously derivatized by phenylboronic acid. The entire sample preparation procedure is completed within 10 min. RESULTS: The assay was proved to be quadratic in the range of 50 to 5000 mgL(-1) with adequate accuracy (96.3-105.8%) and precision (CV ≤ 8.9%). CONCLUSION: The method was successfully applied to quantify the selected compounds in serum of patients from emergency units and the results correlated well with parallel GC-FID measurements (R(2) 0.9933 for ethylene glycol and 0.9943 for glycolic acid).
Keywords: Gas Chromatography-Mass Spectrometry; Time Factors; časové faktory; lidé; analýza nákladů a výnosů; Ethylene Glycol; Glycolates; plynová chromatografie s hmotnostně spektrometrickou detekcí; toxikologie; Cost-Benefit Analysis; Emergencies; glykoláty; ethylenglykol; náhlé příhody; Toxicology; Humans